An Explanatory Factor Analysis of a Brief Self-Report Scale to Detect Neurocognitive Impairment among HIV-Positive Men Who Have Sex with Men and Transgender Women in Peru - Weikum, Damian (AIDS Care, 2017)
Neurocognitive impairment (NCI) has been associated with poor clinical outcomes in various patient populations. This study used exploratory factor analysis (EFA) to examine the factor structure of the existing 95-item Neuropsychological Impairment Scale (NIS) to create a suitable NCI screening instrument for people living with HIV (PLH). In Lima, Peru, 313 HIV-positive men who have sex with men (MSM) and transgender women (TGW) prescribed antiretroviral therapy (ART) completed the NIS using computer-assisted self-interviews (CASI). The EFA used principal axis factoring and orthogonal varimax rotation, which resulted in 42 items with an 8-factor solution that explained 51.8% of the overall variance. The revised, 8-factor, Brief Inventory of Neurocognitive Impairment for Peru (BINI-P) showed a diverse set of factors with excellent to good reliability (i.e., F(1) α=0.92 to F(8) α=0.78). This EFA supports the use of the BINI-P to screen for NCI among Spanish-speaking, HIV-positive MSM and TGW. Future research should examine the effectiveness of the BINI-P in detecting NCI in clinical care settings and the impact of NCI on HIV health-related outcomes, including linkage and retention in care, ART adherence and HIV risk behaviors.